2013
DOI: 10.7243/2050-1218-2-8
|View full text |Cite
|
Sign up to set email alerts
|

Stem cells and cardiac repair: alternative and multifactorial approaches

Abstract: Severe myocardial infarction can lead to ventricular remodelling and progressive contractile dysfunction with inability of the heart to maintain perfusion to vital organs. Pharmacological and surgical interventions can only alleviate symptoms or retard further disease progression. However, these interventions fail to regenerate dead myocardium. Stem cells have the potential to replace or repair dead or injured cells after myocardial infarction. Stem cells are either integrated by themselves or provide a platfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…Commercial vascular grafts are often made of synthetic polyester material, designed to repair damaged blood vessels. In recent times, various devices made of PCL such as vascular grafts, stent materials, and valves have gained much attention because of the possibility of molding it into knitted and woven forms in cardiac surgery (Ahmed, 2013). In this contest, PCL has been blended with a novel biodegradable electroactive PU containing aniline pentamer (AP).…”
Section: Composite Biomaterials For Cardiac Tissue Regenerationmentioning
confidence: 99%
See 1 more Smart Citation
“…Commercial vascular grafts are often made of synthetic polyester material, designed to repair damaged blood vessels. In recent times, various devices made of PCL such as vascular grafts, stent materials, and valves have gained much attention because of the possibility of molding it into knitted and woven forms in cardiac surgery (Ahmed, 2013). In this contest, PCL has been blended with a novel biodegradable electroactive PU containing aniline pentamer (AP).…”
Section: Composite Biomaterials For Cardiac Tissue Regenerationmentioning
confidence: 99%
“…The development of composites is made relatively easier by the nature of polymeric compounds, enabling the association of natural and synthetic polymers to develop scaffolds for both soft (Siddiqui et al, 2018) and hard tissue repair (Iaquinta et al, 2019a). In particular, composite biomaterials have been extensively studied for several application including skin tissue engineering (Chaudhari et al, 2016), nerve (Shafei et al, 2017), and cardiovascular tissue repair (Ahmed, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…MSCs have been proven to be the most beneficial stem cells and their therapeutic applications for MI treatment is rising in comparison with other stem cells. 56 Their outstanding characteristics including the ease of isolation from different tissues, possibility of their largescale expansion, their differentiation ability into cardiomyocyte and vascular cells, their capability of homing toward the inflammation sites, their immunologically tolerance in recipient, the possibility of their systemically IV delivery without cardiac catheterization laboratories and the opportunity of using genetically modified MSCs to improve their engraftment or differentiation potentials make them a popular cell source. 57 It's revealed that MSCs express specific cardiac genes and show cardiomyocyte morphology and contractile activity on the exposure of 5-azacytidine.…”
Section: Mscs In Cardiovascular Diseasementioning
confidence: 99%
“…In the last decade, stem cell therapy for heart diseases has introduced as an alternative option for regeneration of lost cardiomyocytes and vascular endothelium in regenerative medicine. MSCs have been proven to be the most beneficial stem cells and their therapeutic applications for MI treatment is rising in comparison with other stem cells . Their outstanding characteristics including the ease of isolation from different tissues, possibility of their large‐scale expansion, their differentiation ability into cardiomyocyte and vascular cells, their capability of homing toward the inflammation sites, their immunologically tolerance in recipient, the possibility of their systemically IV delivery without cardiac catheterization laboratories and the opportunity of using genetically modified MSCs to improve their engraftment or differentiation potentials make them a popular cell source .…”
Section: Msc In Regenerative Medicinementioning
confidence: 99%
“…Among these scaffolds, the poly(epsilon-caprolactone) (PCL)-based scaffolds are noteworthy [ 36 ]. In fact, PCL is a biodegradable polymer that has been successfully used in vivo and in vitro for regeneration purposes in other tissues such as bone [ 37 , 38 , 39 , 40 , 41 ], cartilage [ 42 , 43 , 44 , 45 , 46 ], osteochondral [ 47 , 48 , 49 , 50 , 51 , 52 ], skin [ 53 , 54 , 55 , 56 , 57 ], nerve [ 58 , 59 , 60 , 61 ], cardiovascular [ 62 , 63 ], musculoskeletal [ 64 , 65 , 66 ], liver [ 67 , 68 , 69 ], and dental [ 70 , 71 , 72 , 73 , 74 , 75 , 76 ] tissue regeneration.…”
Section: Introductionmentioning
confidence: 99%